2019
DOI: 10.4155/fsoa-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Glycemic Control in Patients With Coexisting Melanoma and Diabetes Mellitus

Abstract: Aim:Given the lack of data in the literature, we examined the impact of diabetes mellitus (DM) on melanoma survival and the impact of melanoma on glycemic control.Materials & methods:Patients with melanoma with and without DM were matched 1:1 (2005–2016). Kaplan–Meier analysis was used to estimate overall survival and progression-free survival (PFS). Mixed models compared hemoglobin A1c (HbA1c) and glucose measures over time.Results:Mean HbA1c during the year after cancer diagnosis was 6.7%. The 5-year PFS rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The statistical analyses conducted were similar to those used for our previous studies [13][14][15][16][17][18][19][20]. Patients with DM (cases) and without DM (controls) were compared on the basis of patient demographic and clinical variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical analyses conducted were similar to those used for our previous studies [13][14][15][16][17][18][19][20]. Patients with DM (cases) and without DM (controls) were compared on the basis of patient demographic and clinical variables.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings found statistical significance compared with the other multiple case-control studies done at our institution. The authors had previously investigated the effect of solid tumors -breast, lung, prostate, colorectal, pancreatic, gastric, esophageal, lymphoma and melanoma and DM on patient outcome measures [13][14][15][16][17][18][19][20]. In all these case-control studies, DM did not affect survival of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only exception was for patients with gastroesophageal cancers, where we did find that patients with preexisting DM had a higher risk of death than those without DM [ 26 ]. For patients with melanoma, our analyses revealed an unexpected increase in progression-free survival in the DM group compared with the non-DM group [ 27 ]. The reasons for these differences are not clear; however, further studies should continue to explore these associations, as worldwide incidence of DM continues to rise.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case–control studies of patients at a large cancer institute in the southwestern USA have shown that diabetes does not worsen survival for patients with solid organ cancers and that solid organ cancers do not worsen glycemic control. We have studied this relationship in pancreatic cancer [ 15 ], gastroesophageal cancer [ 16 ], lung cancer [ 17 ], breast cancer [ 18 ], prostate cancer [ 15 ], colorectal cancer [ 19 ] and melanoma [ 20 ]. Gastroesophageal cancer was the only cancer in which a greater risk of death was seen in patients with than without diabetes [ 16 ].…”
mentioning
confidence: 99%